Setaphyes elenae sp. nov., a new species of mud dragon (Kinorhyncha: Allomalorhagida) from Skagerrak (north-eastern Atlantic Ocean) - Cepeda, Diego; González-Casarrubios, Alberto; Sánchez, Nuria; Pardos, Fernando (European Journal of Taxonomy, 2020)
Meiofauna sampling in the proximity of Syd-Hällsö Island (Strömstad, Sweden) revealed a new species of Kinorhyncha from the Skagerrak. The species, Setaphyes elenae sp. nov., is distinguished from its congeners by the arrangement of the middorsal cuticular specializations (it has shortened, distally rounded middorsal processes on segments 1 and 9 and middorsal elevations throughout segments 2–8), as well as by the presence of paired laterodorsal setae on segments 3, 5, 7 and 9 and ventromedial setae on segments 3, 5 and 7 in both males and females. The finding of a new species from the north-eastern Atlantic Ocean, provides new valuable information for the recently established genus in the Allomalorhagida.